Analisis Pengendalian Internal atas Sistem Penggajian ASN dalam Mengatasi Kelebihan dan Kekurangan Pembayaran Gaji - Pandity, Lusia Grasela; Rengga, Andreas Rengga; Tunya, Maria Grasella (Universitas Nusa Nipa Maumere, 2026)
This study aims to analyze the implementation of the internal control system over the payroll system for Civil Servants (ASN) in addressing overpayments and underpayments at the Regional Financial and Asset Management Agency (RFAMA) of Sikka Regency. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The analysis is conducted based on the five components of the Government Internal Control System (GICS), namely control environment, risk assessment, control activities, information and communication, and monitoring. The results of the study indicate thet the implementation of internal controls has been carried out in accordance with regulation, but it is not yet fully optimal. Overpayments and underpayments still occur due to delays in updating personel data, input errors, and delays in issuing Decrees. Strengthening data validation, coordination between units, and regular monitoring are necessary to minimize the risk of payment errors and improve accountability and the quality of regional financial governance